2019
DOI: 10.1177/0959683619831426
|View full text |Cite
|
Sign up to set email alerts
|

New insights into dating the sediment sequence within a landslide-dammed reservoir on the Chinese Loess Plateau

Abstract: The deposition couplets within the check dams and landslide-dammed reservoirs on the Chinese Loess Plateau (CLP) document the processes and histories of watershed soil erosion, transportation and deposition, related to floods, eco-environment and land use changes, and human activities. Previously, dating the couplets was dominantly dependent on multiple intercomparisons among specific sediment yields of visible couplets, 137Cs activities distributions and erosive rainfall events by meteorological records. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The couplet specific sediment yield (CSSY) and annual specific sediment yield (ASSY) were calculated based on the methods of Wang et al (2019) and Wei et al (2018), which were the common ways to estimate the sediment yield within the check dams and landslide‐dammed reservoirs on the CLP. Briefly, the CSSY and ASSY in the JB and HS catchments during A.D. 1850–2000 were determined from Equations and , respectively: CSSYgoodbreak=italicδ·H·()S1goodbreak+S2goodbreak+S1·S23·italicTE·A ASSYgoodbreak=i=1nCSSY where S 1 and S 2 are the top and bottom surface areas of each couplet (m 2 ), respectively; H is the thickness of each couplet (m); δ is the bulk density (1.4 t/m 3 as the mean density of representative sediment samples from check dams and landslide‐dammed reservoirs on the CLP; Zhang et al, 2009); A is the catchment area of the reservoir (m 2 ); TE is the trapping efficiency of the landslide dam (assuming 100% TE due to intact dams since the formation of both reservoirs); n is the number of the couplet within an individual year.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The couplet specific sediment yield (CSSY) and annual specific sediment yield (ASSY) were calculated based on the methods of Wang et al (2019) and Wei et al (2018), which were the common ways to estimate the sediment yield within the check dams and landslide‐dammed reservoirs on the CLP. Briefly, the CSSY and ASSY in the JB and HS catchments during A.D. 1850–2000 were determined from Equations and , respectively: CSSYgoodbreak=italicδ·H·()S1goodbreak+S2goodbreak+S1·S23·italicTE·A ASSYgoodbreak=i=1nCSSY where S 1 and S 2 are the top and bottom surface areas of each couplet (m 2 ), respectively; H is the thickness of each couplet (m); δ is the bulk density (1.4 t/m 3 as the mean density of representative sediment samples from check dams and landslide‐dammed reservoirs on the CLP; Zhang et al, 2009); A is the catchment area of the reservoir (m 2 ); TE is the trapping efficiency of the landslide dam (assuming 100% TE due to intact dams since the formation of both reservoirs); n is the number of the couplet within an individual year.…”
Section: Methodsmentioning
confidence: 99%
“…The chronologies of the JB and HS sequences were built by a multi‐proxy combination of 137 Cs activities, records of recent rainfall and historical flood grade indexes, annual freeze–thaw layers that were identified by high concentrations and correlations of Ca and Fe (Wang et al, 2016b). Details of the methods used for sampling, couplets division, and dating for the JB and HS sequences were reported by Wang et al (2019, 2021). As a result, the JB sequence consisted of 126 couplets in 78 individual years over A.D. 1855–2014, which indicated that the JB sequence was deposited by 126 hydrological events at 78 individual years during this period.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations